First data on the chemical composition of natural waters at the gold deposit “Novye Peski” (South Karelia, Russia) - Sidkina Evgeniya; Konyshev Artem; Cherkasova Elena; Toropov Andrey; Vorobey Sofia (E3S Web of Conferences, 2024)
Actual analytical methods make it possible to precisely determine a of chemical elements contained in water, including for the purpose of assessing the ecological state of the environment in connection with mining activities. The object of this research is the natural waters of the gold deposit “Novye Peski” located in the Pryazhinsky region (Republic of Karelia, Russia). Analytical data indicate that the geochemical background of the region is exceeded for most of the chemical elements. Research results indicate that the geochemical background of the region is exceeded for most of the considered chemical elements and ions, which can be divided into three groups: 1) the highest concentrations were determined in quarry water (Zn, As, Mo, U, Ni, Cu, Sr, Li, B, as well as Ca 2-); 2) the content is at the same level in all and other cations, HCO3samples (Al, Si, V, Ti, Ba); 3) the highest content in stream and tailing pond (Fe, Mn). We assume that the main factor influencing the behavior of elements of the first group is mining, and for the third is the presence of dissolved organic matter high content with the formation of metal-organic species in water.